1996
DOI: 10.3989/graellsia.1996.v52.i0.376
|View full text |Cite
|
Sign up to set email alerts
|

A key, based on wing patterns of biting midges (genus <i>Culicoides</i> Latreille - Diptera: Ceratopogonidae) in the Iberian Peninsula, for use in epidemiological studies

Abstract: The identity of vectors of disease are often required speedily in epidemiological studies but with a precision which excludes as many other species as possible. Identification keys usually require the examination of many different parts of the suspected vector to pinpoint the species. This consumes considerable time and resources, so epidemiologists tend to ignore them. A simplified approach to identification is proposed, using the characteristics of a single part of the body (the wings) of biting midges of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 12 publications
0
59
0
3
Order By: Relevance
“…So biting midges trapped were identified only at basic phenotypic level to determine if they belong to the genus Culicoides. In addition, the basic phenotypic identification of all midges captured showed that all specimens corresponded to the Culicoides variipennis complex (Coquillett) (Wirth, 1957;Borror et al, 1989;Rawlings, 1996). Midges of C. variipennis complex comprise the species C. variipennis, C. sonorensis and C. occidentalis (Schmidtmann et al, 2011;Tabachnick, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So biting midges trapped were identified only at basic phenotypic level to determine if they belong to the genus Culicoides. In addition, the basic phenotypic identification of all midges captured showed that all specimens corresponded to the Culicoides variipennis complex (Coquillett) (Wirth, 1957;Borror et al, 1989;Rawlings, 1996). Midges of C. variipennis complex comprise the species C. variipennis, C. sonorensis and C. occidentalis (Schmidtmann et al, 2011;Tabachnick, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Previous separation of other captured insects, Culicoides (Culicoides, Diptera: Ceratopogonidae) were identified with the aid of a binocular stereoscopic microscope (Carl Zeiss) according to the characteristics observed in the wings as reported by Rawlings (1996) and Borror et al (1989). The identification is based on the characteristic pattern of dark and light areas of the wings, the dorsal side of the thorax, size and shape of the segment of the antennas, the relative position of the eyes, the shape of the spermathecal in females and the shape of the genitals in males (Meiswinkel et al, 2004;Werner and Kampen, 2007).…”
Section: Identification Of Specimensmentioning
confidence: 99%
“…One female had sensillae coeloconica in antennal segment 4, and was lacking in the 12 th , whereas another female had sensillae coeloconica in the 6 th segment. (Khalaf 1961) and C. odiatus female (Austen 1921) and male (Edwards 1939) has been widely accepted (Boorman 1989;Glukhova 1989;Rawlings 1996). However diff erences in thoracic pattern and male genitalia can be detected when comparing original descriptions of both species.…”
Section: Culicoides Indistinctus Khalaf 1961mentioning
confidence: 99%
“…Culicoides are initially identified under a stereomicroscope at species-group level according to wing pattern morphology, using main taxonomic keys for palaearctic Culicoides [56][57][58][59][60]. Specimens will then be identified down to species level.…”
Section: Identification Methodsmentioning
confidence: 99%